Health inequity in pandemic anxiety about COVID-19 infection and socioeconomic consequences in Japan: A structural equation modeling approach - Kyoko Shimamoto; Eoin McElroy; Yoko Ibuka (Elsevier, 2022)
Background: Health inequity in relation to COVID-19 infection and socioeconomic consequences is a major global concern. Mental health issues in vulnerable populations have received special attention in research and practice during the COVID-19 pandemic. However, there is limited evidence on the nature of the anxieties experienced as a result of COVID-19, and how such concerns vary across demographic groups. Aim: This study examines anxiety among the working population of Japan (aged 18-59), in terms of both COVID-19 infection and socioeconomic consequences, using an internationally validated tool, the Pandemic Anxiety Scale (PAS). Methods: Data were collected using an online survey (n = 2,764). The analyses included an exploratory factor analysis (EFA), a confirmatory factor analysis (CFA), and structural equation modeling (SEM), followed by validation of the Japanese version of the PAS. Results: A two-factor latent variable model shows the multidimensionality of anxiety in regard to the COVID-19 pandemic and the disparity across population groups in predicting the two defined anxiety dimensions. Several path coefficients showed somewhat unexpected and/or unique results from Japan compared with previous European studies. Specifically, self-reported health status was not significantly related to disease anxiety, and those who were not in paid employment reported lower consequence anxiety. The SEM results showed a greater number of significant exogenous variables for consequence anxiety compared to disease anxiety, highlighting disparities in pandemic anxiety by socioeconomic status in regard to socioeconomic consequences of the pandemic. Conclusion: In contrast to existing European studies, evidence from the current study suggests contextual patterns of health inequity. Due to the prolonged socioeconomic consequences of the pandemic, multidisciplinary research on mental health issues and the quality of life remains an important research agenda in exploring socioeconomic measures in context, towards addressing inequity concerns.